Associations between common variants in FTO and near MC4R genes on BMI, waist circumference, and type 2 diabetes prevalence among Hispanic and non-Hispanic White individuals: the San Luis Valley Diabetes Study - Sayer, Richard Drew, author; Nelson, Tracy L., advisor; Hickey, Matthew S., committee member; Peel, Jennifer L., committee member; Hokanson, John, committee member (Colorado State University. Libraries, 2011)
Introduction: The prevalence of obesity and type 2 diabetes (T2D) has risen sharply in the United States over the previous 40 years. Heritability estimates for obesity are generally high, and suggest that people may have genotypes that predisposes them to obesity when confronted with an obesogenic environment. Genetic variants in FTO and near MC4R genes have consistently been shown to be associated with risk of obesity. Methods: Utilizing data from the third examination of the San Luis Valley Diabetes Study (1997-1998, n = 837), we determined the minor allele frequency (MAF) and genotype distribution of single nucleotide polymorphisms (SNP)s rs8050136 and rs17782313 in a cohort of Hispanic and non-Hispanic white individuals. The associations between SNPs rs8050136 and rs17782313 and body mass index (BMI), waist circumference (WC), total energy intake, and T2D prevalence rates were determined. Results: MAFs and genotype distributions varied between Hispanics and non-Hispanic whites for both SNPs. Hispanics were less likely to be carriers of high-risk A allele at rs8050136 (MAF: 25% vs. 38.3%) and the high-risk T allele at rs17782313 (17% vs. 23.3%) than non-Hispanic whites. After controlling for age, there was a significant association between the rs8050136 SNP in FTO and BMI in all Hispanics (p = 0.0018) and Hispanic men (p = 0.0007), but the association was not significant in Hispanic women (p = 0.14). Among all Hispanics, homozygous carriers of the FTO high-risk A allele had an average BMI of 31.1 kg/m2 (95% CI: 29.0-33.1) compared to an average BMI of 27.1 kg/m2 (95% CI: 26.4-27.8) in homozygous carriers of the C allele. In Hispanic men, homozygous carriers of the high-risk A allele had an average BMI of 31,4 kg/m2 (95% CI: 28.5-34.3) compared to 25.9 kg/m2 (95% CI: 25.0-26.9) in homozygous carriers of the C allele. After controlling for age, there was also a significant association between the rs8050136 SNP and WC in Hispanic men (p = 0.0048), but not Hispanic women (p = 0.24). Hispanic male homozygous carriers of the A allele had an average WC of 104.2 cm (95% CI: 97.7-110.7) compared to an average WC of 94.1 cm (92.0-96.2) in homozygous carriers of the C allele. A high dietary fat intake was shown to modify the association between the FTO variant and BMI. No other significant associations were found between genetic variants in FTO or near MC4R on BMI, WC, total energy intake, or T2D prevalence. Discussion: Hispanics are less likely to be carriers of high-risk alleles in FTO (rs8050136) and near MC4R (rs17782313) than non-Hispanic whites. Our analysis demonstrates that the FTO variant is associated with BMI and WC in Hispanics and also that this relationship between the FTO variant and BMI is modified by dietary fat intake.